Role of endoscopic surgery in the management of sinonasal and skull base schwannomas. (15th February 2016) - Karligkiotis, Apostolos; Turri‐Zanoni, Mario; Sica, Eleonora; Facco, Carla; Freguia, Stefania; Mercuri, Anna; Pistochini, Andrea; Bignami, Maurizio; Castelnuovo, Paolo
Abstract: Background: The purpose of this study was to report our experience with the endoscopic management of sinonasal schwannomas, analyzing the advantages, limitations, and outcomes of the technique. Methods: A retrospective analysis was carried out on 11 patients treated endoscopically between 2000 and 2014 at a single institution. Results: Eight patients underwent an exclusive endoscopic endonasal approach, whereas, in 3 patients, an osteoplastic flap was combined because of massive or lateral frontal sinus involvement. The tumor extended into the orbit in 5 cases, and involved the skull base in 5 patients who required a concomitant endoscopic duraplasty. No evidence of disease was observed in 10 patients after a mean follow‐up of 90.1 months (range, 14–189 months). One patient was alive with persistence of disease, although asymptomatic. Conclusion: The endoscopic endonasal approach is a valid alternative for the vast majority of sinonasal schwannomas with minimal morbidity for the patient. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E2074–E2082, 2016